2003
DOI: 10.1021/ja029018v
|View full text |Cite
|
Sign up to set email alerts
|

Doubly N-Confused Hexaphyrin:  A Novel Aromatic Expanded Porphyrin that Complexes Bis-metals in the Core

Abstract: Meso-hexakis(pentafluorophenyl)-substituted doubly N-confused hexaphyrins and their metal complexes were synthesized for the first time, and the structures were elucidated by X-ray single-crystal analyses. The free base form of oxidized hexaphyrin (5) had two preorganized N3O pockets in the macrocyclic core, where a hydrogen-bonding network was formed to keep the molecule planar (the mean plane deviation is 0.054 A). The formation of a planar bis-Cu(II) complex was confirmed by UV/vis, magnetic susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 5 publications
2
99
0
12
Order By: Relevance
“…[115] Im Folgenden konzentrieren wir uns hauptsächlich auf die reinen Azasysteme und einige ihrer Heteroanaloga. Auslassen werden wir dagegen die Makrocyclen mit N-invertierten Pyrrolen, [233,234] [238] das antiaromatisch ist und die Figure-Eight-Konformation (T2 0 ) annimmt. Ein analoges Redoxpaar wurde später für die meso-trifluormethylierten Derivate gefunden.…”
Section: Rubyrineunclassified
“…[115] Im Folgenden konzentrieren wir uns hauptsächlich auf die reinen Azasysteme und einige ihrer Heteroanaloga. Auslassen werden wir dagegen die Makrocyclen mit N-invertierten Pyrrolen, [233,234] [238] das antiaromatisch ist und die Figure-Eight-Konformation (T2 0 ) annimmt. Ein analoges Redoxpaar wurde später für die meso-trifluormethylierten Derivate gefunden.…”
Section: Rubyrineunclassified
“…[7] In contrast, in the hexaphyrin system, the doubly N-confused dioxohexaphyrins are rather stable and can even be derived from standard hexaphyrins, [8] while the corresponding fused species have not yet been found. Here the question arises as to the relationship between the fate of the confused pyrrole ring and the size of the macrocycles, especially in the sapphyrin system, an intermediate compound between porphyrins and pentaphyrins, and perhaps the oldest member of the expanded porphyrin family.…”
mentioning
confidence: 94%
“…The formation of 2 during the synthesis of 1 clearly shows that the ring fusion is a usual phenomenon among N-confused pentapyrrolic macrocycles. [7,8] Our synthetic studies show that 2 can be formed only as a side product when 1 is synthesized by a [5+0] route (path a). We found that 2 can also be made directly from 1 by following a similar strategy as used for the synthesis of NFP [6] (path c).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…on silica gel and treatment with aqueous NH 4 Cl, the inverted sapphyrin 3 was obtained in 8 −9% yield (Scheme 1).…”
mentioning
confidence: 99%